Insights into Imaging - Marti-Bonmati, Luis
Insights into Imaging is a peer-reviewed open access journal published under the brand SpringerOpen. All content is freely available online to anyone, anywhere! Insights into Imaging was founded by the European Society of Radiology (ESR) in order to create a platform for educational material, guidelines and recommendations, topics of controversy and formal statements concerning European radiology. It continuously updates scientific and best-practice knowledge in radiology through the publication of original articles and state of the art reviews, opinions, along with recommendations and statements from the leading radiological societies in Europe. A thorough and competent peer review procedure serves the authors’ need for critical feedback. A well balanced combination of review articles, original papers, short communications from European radiological congresses and information on society matters makes I³ an indispensable source for current information in this field. I³ is owned by the ESR, however authors retain copyright to their article according to the Creative Commons Attribution License (see Copyright and License Agreement). All articles can be read, redistributed and reused for free, as long as the author of the original work is cited properly. Insights into Imaging is the official journal of the following organisations: European Society of Cardiac Radiology (ESCR) European Society of Emergency Radiology (ESER) European Society of Gastrointestinal and Abdominal Radiology (ESGAR) European Society for Hybrid Medical Imaging (ESHI) European Society of Head and Neck Radiology (ESHNR) European Society of Molecular and Functional Imaging in Radiology (ESMOFIR) European Society of Neurology (ESNR) European Society of Oncologic Imaging (ESOI) European Society of Musculoskeletal Radiology (ESSR) European Society of Thoracic Imaging (ESTI) European Society of Urogenital Radiology (ESUR) European Society of Breast Imaging (EUSOBI) European Society of Medical Imaging Informatics (EuSoMII).